Variable-Speed Operation of Micro-Hydropower Plants in Irrigation Infrastructure: An Energy and Cost Analysis - Arsenio Barbón; Francisco González-González; Luis Bayón; Ramy Georgious (Applied Sciences, 2023)
Micro-hydropower plants have now become a way to decarbonise the power generation system. Older micro-hydropower plants generally operate at a fixed speed. When there is a lack of rainfall, these plants operate outside their design flow causing various problems (such as the occurrence of the phenomenon of cavitation, decreased turbine performance, and decreased operating hours), especially in micro-hydropower plants installed in irrigation infrastructure, where the priority for water use is crops. This study aims to carry out a comparative evaluation of several indicators (cavitation, investment costs, electricity production and economic benefit) of two types of control system on an asynchronous electric generator (a fixed speed control system (scenario 1) and a variable-speed control system (scenario 2)) at the same micro-hydropower plant. The Rebolluelo micro-hydropower plant (Spain) is used for this purpose as a case study. This micro-hydropower plant uses a semi-Kaplan turbine coupled to an asynchronous electric generator through a gearbox. The results show the advantages of using a variable-speed control system. The use of variable-speed technology: (i) eliminates the possibility of cavitation, (ii) increases the power output ratio (from <semantics>35.87%</semantics> to <semantics>93.03%</semantics>), and (iii) increases the economic benefit (from <semantics>29.31%</semantics> to <semantics>108.72%</semantics>). There are also, of course, disadvantages, such as an <semantics>11.96%</semantics> increase in cost. This work demonstrated the superiority of variable speed technology at micro-hydropower plants for three of the four indicators evaluated. This work could be of assistance when making decisions regarding future micro-hydropower plant installations.